Using the ClickUp application to streamline administrative workflows for creation interactive educational content - Khmil, Anastasiia; Khmil, Nataliia (My University, 2024)
У публікації висвітлюються практичні аспекти використання програми ClickUp для впорядкування адміністративних робочих процесів створення інтерактивного освітнього контенту The article highlights the practical aspects of using the CLICKUP program to streamline administrative workflows for creating interactive educational content
Khmil A. Using the ClickUp application to streamline administrative workflows for creation interactive educational content / A. Khmil, N. Khmil // Information technologies in the modern world: research of young scientists": Materials of the International scientific-practical conference of young scientists, postgraduates and students ": abstracts of reports, (February 22-23, 2024.). – Kharkiv.: Simon Kuznets Kharkiv National University of Economics, 2024. – P. 171–172.
Keywords: програма ClickUp, створення, інтерактивний освітній контент; ClickUp program, creation, interactive educational content